Challenges of Antarctic Plant Production. Lessons learned from the deployment and preliminary operational results from the EDEN ISS project - Bamsey, Matthew; Schubert, Daniel; Zeidler, Conrad; Vrakking, Vincent; Zabel, Paul; Kohlberg, Eberhard (2018)
Dating back as far as the early 1900s, people have been constructing plant production systems in Antarctica. In the early years, these plant production systems were typically small and expeditioner driven. Current systems, such as the EDEN ISS Mobile Test Facility are more complex, use the latest in controlled environment agriculture technology and begin to provide non-negligible impact on overwintering crew diets while minimizing their environmental footprint. Although EDEN ISS, like other Antarctic greenhouse projects focuses on providing fresh food to overwintering crewmembers, it differs from the bulk of these projects in that it has the primary focus of taking advantage of Antarctica’s remoteness, extreme environment and stringent environmental regulations to advance space-based production systems. The EDEN ISS project also distinguishes itself from many other Antarctic greenhouse projects in that its development involved several years of planning and design mirroring space system development pathways. This includes a space systems engineering focused process throughout its design, testing and then subsequent deployment and operational phase. This work presents a number of the key lessons learned from the EDEN ISS design phase; assembly, integration and test phase; two month field team deployment phase and from the facility’s first few months of operation. Preliminary results from the facility, including leakage, crew time requirements, water use, acoustic tests and power requirements are also presented. These and the results of an assessment of the implemented space system design process are described so as to help future Antarctic greenhouse developers and those using Antarctica as a space analogue site for this purpose, to refine their initial assumptions and improve their overall designs.